Students’ Perceptions towards Hybrid Learning The Case of Master One EFL Students at Mohamed Cherif Messaadia University of Souk-Ahras - NOURI Abd El Krim (My University, 2022)
Abstract The purpose of this study is to conduct an exploratory research for the sake of investigating students’ perceptions towards hybrid learning program in the Department of English at Mohamed Cherif Messaadia University, in Souk-Ahras. In order to test our hypothesis which suggests that EFL Master 1 students at MCM University have positive perceptions towards hybrid learning, we have designed and distributed an online questionnaire to 80 master 1 students which constitute the sample of the study. The participants have already taken part in hybrid courses during the spread of COVID-19 pandemic in the academic year 2021-2022. Participants responded to the questionnaire which included three sections through which we sought to gather information concerning demographics, personal attributes, weaknesses and strengths of hybrid learning and reasons for taking (participating in) a hybrid course. One of the major findings indicated that 78% of the students surveyed had positive perceptions towards the hybrid learning course in which they had participated. The gathered data, on the other hand, has illustrated that hybrid learning had a positive impact on EFL Master 1 students at MCM University in the sense that it facilitated learning for students in classroom, and made them more aware and conscious of their learning. Based on these results, the hypothesis is confirmed. Moreover, the majority of the students surveyed designated that they would participate in another hybrid course if they get the opportunity in the future.